Information literacy practices by teacher-librarians: a case of four mara junior science colleges in kedah, malaysia - Baharuddin, Mohammad Fazli; Mohd Saad, Mohd Sharif; Mohd Nadzar, Fuziah (Persatuan Pustakawan Malaysia, 2011)
This paper discusses the results of a study carried out at four selected MARA Junior Science Colleges (MJSC) in Kedah, Malaysia. It focuses on teachers’ perception on information literacy practices by teacher-librarians or library media teachers. MJSCs are boarding secondary schools managed by Majlis Amanah Rakyat (MARA), a statutory body in Malaysia that run 42 MJSCs nation-wide and employs a teacher-librarian or library media teacher at each MJSC. Teacher-librarians only teach seven hours per week and spend most of their working hours managing their school resource centres. The objectives of this study are: to identify the perception of MJSC teachers on the roles of teacher-librarians; to find out the practices of information literacy by teacher-librarians in the schools; and to identify the collaborative effort that are being practiced between teachers and teacher-librarians. Respondents are school teachers from four MJSCs in Kedah who are teaching various subjects. The instrument used was adapted from a questionnaire developed by the Council on Teacher Education (C.O.T.E) (2003). From 200 questionnaires distributed, 157 questionnaires were returned. About 47.8% of the teachers were unsure about information literacy. Many respondents admitted that teacher-librarians have been performing the roles very well but they are unsure of the roles of the teacher-librarians.